"I'm not the woman I was": Women's perceptions of the effects of fibromyalgia on private life. Issue 8 (2nd August 2016) - Briones-Vozmediano, Erica; Vives-Cases, Carmen; Goicolea, Isabel
ABSTRACT: In this qualitative study, we explored how gender shapes women's experiences of living with fibromyalgia and how it affects their private lives. Through thematic analysis of data from 13 in-depth interviews in Spain, we identified seven themes which reflect that these women feel remorse and frustration for not being able to continue to fulfill the gender expectation of caring for others and for the home. This research contributes to a better understanding of what suffering from fibromyalgia implies for women and provides insights into how families and providers can support women with fibromyalgia in order to achieve a beneficial lifestyle.